**Answer:**

y = (2/7)x -12 (Answer Choice B)

**Step-by-step explanation:**

Take the given values ( m=2/7 and y-intercept (0,-12) ) and substitute them into y = mx + b:

**y = (2/7)x -12**

Let S be the sum of the first n terms of the left side:

Multiply both sides by 2/3 :

Subtract this from S :

Solve for S :

As n gets larger and larger, S converges to the given sum, and the term (2/3)ⁿ⁺¹ converges to zero, which leaves us with

The value of the expression decreases

**Answer: hello your question is poorly written attached below is the complete question**

answer:

1 ) = I (

2) = F

3) = Z

4) = D

**Step-by-step explanation:**

**attached below is the required solution.**

1 ) = I ( The sequence diverges to infinity )

2) = F ( The sequence has a finite non-zero limit )

3) = Z ( The sequence converges to zero )

4) = D ( The sequence diverges )

**Answer:**

Eqivelent expressions

**Step-by-step explanation:**

also dis